Molecular evidence for genetic exchanges among ribosomal genes on nonhomologous chromosomes in man and apes. - Arnheim, N (1980)
We have found that human and ape ribosomal genes undergo concerted evolution involving genetic exchanges among nucleolus organizers on nonhomologous chromosomes. This conclusion is based upon restriction enzyme analysis of the ribosomal gene families in man and five ape species. Certain structural features were found to differ among (but not within) species even though the ribosomal genes have a multichromosomal distribution. Genetic exchanges among nucleolus organizer regions may be related to the well-known phenomenon of acrocentric chromosome associations observed in man and apes. Length variation in a region of the nontranscribed spacer was found in both chimpanzee species we examined. The nature of this length variation was found to be identical to that previously described in man. The origin of the length variation and its polymorphism within these three species might be explained by unequal alignment and unequal cross-over among the ribosomal genes. An especially surprising finding was a nucleotide sequence polymorphism present in each individual human and ape we examined. Some ribosomal genes of each individual have a HindII site in the 28S gene about 800 base pairs from the EcoRI site in this gene. The remaining 28S genes lack this HindII site. The presence of this polymorphism within individuals of every species we examined suggests that it has been maintained by natural selection.